2020
DOI: 10.1002/pri.1849
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐rater reliability of activity measure for post‐acute care6‐Clicks’ inpatient mobility short form in the intensive care unit

Abstract: Objective: Examine the inter-rater reliability of the activity measure for post-acute care (AM-PAC) inpatient mobility short form (IMSF) when completed by physical therapists (PTs), during routine clinical practice, in a variety of patients with critical illness. Methods: A prospective observational evaluation at single, large academic hospital in the United States. Patients (n = 76) in surgical, medical and neurological intensive care units (ICUs) were evaluated as part of routine clinical practice using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…The '6-Clicks' tool is a commonly used instrument to measure mobility (Jette et al, 2007;Jette et al, 2014aJette et al, , 2014b in acute and post-acute settings (Dima et al, 2020;Hiser et al, 2020;Hoyer et al, 2018). In this study, the lowest level of convergent validity was seen in the Orthopaedic admitting service.…”
Section: Discussionmentioning
confidence: 65%
“…The '6-Clicks' tool is a commonly used instrument to measure mobility (Jette et al, 2007;Jette et al, 2014aJette et al, , 2014b in acute and post-acute settings (Dima et al, 2020;Hiser et al, 2020;Hoyer et al, 2018). In this study, the lowest level of convergent validity was seen in the Orthopaedic admitting service.…”
Section: Discussionmentioning
confidence: 65%
“…The AM‐PAC is scored based on the amount of assistance a patient needs to complete specific mobility tasks (e.g., getting out of bed) and is completed by clinicians based on patient input, observation, clinician judgment or input from family members of a patient's capacity for mobility. It has been shown to be valid in this population and to have excellent interrater reliability between nursing and physical therapy (Hiser et al, 2020; Hoyer et al, 2017; Jette et al, 2015). The JH‐MGC is displayed in Figure 1 with AM‐PAC scores on the left and corresponding JH‐HLM goals on the right.…”
Section: Methodsmentioning
confidence: 99%
“…11 In clinical practice at Essentia Health, total scores and percent impairment are calculated in the EHR based on item scores entered into an electronic flowchart by occupational and physical therapists. In this study, scale scores were calculated from total scores to allow for comparison with research by Jette et al 9 Previous research on the reliability of 6-Clicks showed high overall intraclass correlation coefficients in the general acute care patient population (daily activity=0.783, basic mobility=0.849), 11 within an intensive care unit (ICU) patient population (basic mobility=0.957), 20 and within a neuroscience inpatient department (basic mobility: physical therapist pairs=0.91, nurse pairs=0.97). 21 However, intraclass correlation coefficient ranges between rater pairs were more variable in the general acute care patient population, as were weighted kappa scores, with more variability seen between occupational therapists than physical therapists.…”
Section: Instrumentmentioning
confidence: 99%